2021
DOI: 10.3390/ph14050396
|View full text |Cite
|
Sign up to set email alerts
|

Terbium-Based AGuIX-Design Nanoparticle to Mediate X-ray-Induced Photodynamic Therapy

Abstract: X-ray-induced photodynamic therapy is based on the energy transfer from a nanoscintillator to a photosensitizer molecule, whose activation leads to singlet oxygen and radical species generation, triggering cancer cells to cell death. Herein, we synthesized ultra-small nanoparticle chelated with Terbium (Tb) as a nanoscintillator and 5-(4-carboxyphenyl succinimide ester)-10,15,20-triphenyl porphyrin (P1) as a photosensitizer (AGuIX@Tb-P1). The synthesis was based on the AGuIX@ platform design. AGuIX@Tb-P1 was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…When we added P1 to the nanoparticle, P1 fluorescence increased twice as Tb peaks decreased, demonstrating the energy transfer between Tb and P1. The same observation was made experimentally in a previous work dealing with the same nanoplatform under X-ray exposure [ 29 ]. Our simulations revealed that scintillation PDT can be dramatically improved when scintillators are added to the PS.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…When we added P1 to the nanoparticle, P1 fluorescence increased twice as Tb peaks decreased, demonstrating the energy transfer between Tb and P1. The same observation was made experimentally in a previous work dealing with the same nanoplatform under X-ray exposure [ 29 ]. Our simulations revealed that scintillation PDT can be dramatically improved when scintillators are added to the PS.…”
Section: Discussionsupporting
confidence: 79%
“…With Cerenkov radiations also emitting UV light, potential bias would have flawed our results. Nevertheless, when we exposed AGuIX@Tb or AGuIX@Gd to high energy photons, we did not observe any SOSG increase at the activity concentrations used in our previous experiments [ 29 ].…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations